Young People's Creative and Performing Arts Participation and Arts Self‐concept: A Longitudinal Study of Reciprocal Effects. (23rd April 2016) - Mansour, Marianne; Martin, Andrew J.; Anderson, Michael; Gibson, Robyn; Liem, Gregory A.D.; Sudmalis, David
Abstract: This longitudinal study examines the relationship between young people's creative and performing arts participation (e.g., in dance, drama, film, music, visual arts) and their arts self‐concept. Drawing on the positive youth development (PYD) framework and the reciprocal effects model (REM) of self‐concept, a cross‐lagged panel design is implemented to explore the connections between arts self‐concept and each of school (e.g., school‐based arts instruction), home (e.g., parent–child arts interaction), and community (e.g., out‐of‐school arts instruction) creative and performing arts participation. The study drew on an Australian sample of 643 elementary and high school students from 15 schools. Analyses showed that beyond the effects of socio‐demographics and prior achievement, there are longitudinal associations (including reciprocal effects) between numerous forms of creative and performing arts participation and arts self‐concept. Implications are discussed.